INTERNATIONALIZATION AND CORPORATE GOVERNANCE: A PERFORMANCE ANALYSIS OF BRAZILIAN PUBLICLY TRADED COMPANIES - Priscila de Oliveira; Catarine Palmieri Pitangui Tizziotti; Fernanda Maciel Peixoto; Aracy Araújo (Revista Gestão em Análise, 2022)
This paper aims to conduct a comparative analysis between internationalized and non-internationalized publicly traded companies and their performances, considering ROA and ROE within the corporate governance listing segments they occupy in B3 for 2017. For this, the averages and standard deviations of 152 Brazilian non-financial institutions by sector, belonging to the Economática database (2017), were confronted. This research can be classified as descriptive, quantitative in nature with the use of statistical methods and techniques. As variables of internationalization of the companies, exports over total revenue and trading of ADRs were used. As for corporate governance, we followed the classification of the B3's CG listing segments. The results showed that most sectors show a positive relation for companies with high governance and that is internationalized, indicating that companies with this profile tend to have better performance, considering the variables studied: ROA and ROE. It is suggested, as future research, the inclusion of other performance variables, increase the period of analysis, and use other statistical tests.